Differences of water chemistry, bird assemblages and nutrient loads introduced by waterbirds into morphologically similar waterbodies - Gwiazda Robert; Kosiba Joanna (Oceanological and Hydrobiological Studies)
The number and structure of waterbirds is affected by the size of the waterbody, the presence of islands and macrophytes, but also by their trophy status. The aims of the study were to compare nutrients in water, numbers of waterbird assemblages, and the loading of nitrogen and phosphorus introduced by waterbirds in two similar waterbodies with different rates of water discharge. This study was conducted in two eutrophic shallow waterbodies, P1 and P2 in 2016 and 2017. The median concentrations of NO2-, NO3- and NH4+ were 4.0 times, 3.2 times, and 1.7 times greater in the P1 than in the P2 location, respectively. Similar proportions of organic matter in sediments were statistically greater in P1. The number of birds was also significantly greater in P1 than in P2. The waterbirds (Anas platyrhynchos, Aythya fuligula, Fulica atra, Phalacrocorax carbo and Chroicocephalus ridibundus) excreted 5.2 times more total phosphorous and 3.3 times more total nitrogen in P1 than in P2. Significant negative correlations were also found between the concentrations of NO3- and the number of waterbirds in P1.